Qualitative Evaluation of a Community-Based Physical Activity and Yoga Program for Men Living With Prostate Cancer: Survivor Perspectives - SN Culos-Reed PhD; M Dew MSc, CSEP-CEP; J Shank MSc; DM Langelier MD, MSc; M McDonough PhD (SAGE Publishing, 2019)
Purpose Physical activity (PA) programs for prostate cancer survivors have positive effects on many aspects of health-related quality of life. Translating this research into sustainable community-based settings is necessary to ensure access to programs for survivors. This study examines patient perspectives in the community-based TrueNTH Lifestyle Management (TrueNTH LM) program in Calgary, Canada. Methods Eleven men from programs at civic wellness centers participated in 2 small semistructured focus groups (n = 5 and 6) at the University of Calgary. Motivation for program initiation and adherence, benefits and barriers to participation, and individual satisfaction and feedback on program improvement were discussed. Audio recordings were transcribed and analyzed using thematic methodology guided by a pragmatic philosophy on the patient experience in the program. Results Themes identified included perceived benefits of participating (physical, psychological, and social), facilitators for involvement in the PA program (program design, initial free access, tailored to prostate cancer specific needs, psychosocial environment), and opportunities for improvement and sustainability (exercise as a part of standard care, cost structure, home-based options). Conclusions These findings provide valuable insight into patient perspectives on effective characteristics of prostate cancer and exercise programs. TrueNTH LM has implemented findings, and ensuring needs (benefits and barriers) are addressed for prostate cancer survivors when entering community-based PA programs.